FAKTOR YANG MEMPENGARUHI NET PROFIT MARGIN (NPM) PADA BANK NEGARA INDONESIA (BNI) PERSERO CABANG PALANGKA RAYA - Sunarmie Sunarmie (Al-Kalam Jurnal Komunikasi, Manajemen dan Bisnis, 2022)
Indonesia gained different net profit margins. Banks with the highest net profit margin for four consecutive periods, each of which exceeds 24%, while bank with the lowest NPM is Bank Negara Indonesia (BNI), of which value was less than 10.22% in 2016, even in 2019, NPM obtained by Bank BNI was negative showing that the bank suffered a loss during the period 2019. Different from 9 other banks with NPM value relatively stable, the lowest NPM value was obtained by BNI, particularly in 2019. Interestingly, given BNI is one of the ten banks in Indonesia having the biggest asset, it merely obtained a low NPM. This study aimed to (1) identify the effect of operational efficiency ratio and cost efficiency ratio on net profit margin of Bank Negara Indonesia (BNI) Persero simultaneously during the period of 2014-2021 and (2) to identify the effect of operational efficiency ratio and cost efficiency ratio on net profit margin of Bank Negara Indonesia (BNI) Persero partially during 2014-2021. This is a descriptive qualitative study which reveals the degree of an effect or relation between variables stated in figures. It was done in such a way by collecting data which is supporting factors of the effect between relevant variables to be analyzed later. The results suggested that Operational efficiency ratio (BOPO ratio) and cost efficiency ratio (CER) bring an effect of 91.6% in illustrating each variation to net profit margin (NPM) value of Bank BNI between 2014 and 2021, while the remaining of 8.4% is illustrated by other variables out of research model, such as interest sensitivity rate (ISR). The conclusion of this study results include (a) operational efficiency ratio (BOPO ratio) partially brings an adverse effect, while cost efficiency ratio (CER) in fact brings a positive effect. In case of Bank BNI, this is a result of the development of total non-interest expense, as an indicator of CER, in fact it can boost total sales which is an indicator of NPM, particularly in 2019, where the total sales increased when the bank suffered a loss, and (c) two free variables, namely variable X1, operational efficiency ratio (BOPO ratio) partially dominantly affecting binding variables, brings an effect on net profit margin (NPM).